Ant-Man and the Wasp [videorecording (DVD)] - Reed, Peyton; Rudd, Paul; Rudd, Paul; Lilly, Evangeline, 1979-; Peña, Michael, 1976-; Lee, Stan, 1922-2018 (Walt Disney Home Entertainment, 2018)
Ant-Man is on a new mission with Hank Pym and his daughter Hope van Dyne where they have to retrieve Hope's mother known as the Wasp from the quantum realm.